Effect of Meteoric Ions on Ionospheric Conductance at Jupiter. Issue 3 (28th March 2022) - Nakamura, Yuki; Terada, Koichiro; Tao, Chihiro; Terada, Naoki; Kasaba, Yasumasa; Leblanc, François; Kita, Hajime; Nakamizo, Aoi; Yoshikawa, Akimasa; Ohtani, Shinichi; Tsuchiya, Fuminori; Kagitani, Masato; et al.
Abstract: Ionospheric Pedersen and Hall conductances play significant roles in electromagnetic coupling between the planetary ionosphere and magnetosphere. Several observations and models have suggested the existence of meteoric ions with interplanetary origins in the lower part of Jupiter's ionosphere; however, no models have considered the contributions of meteoric ions to ionospheric conductance. This study is designed to evaluate the contribution of meteoric ions to ionospheric conductance by developing an ionospheric model combining a meteoroid ablation model and a photochemical model. We find that the largest contribution to Pedersen and Hall conductivities occurs in the meteoric ion layer at altitudes of 350–600 km due to the large concentration of meteoric ions resulting from their long lifetimes of more than 100 Jovian days. Pedersen and Hall conductances are enhanced by factors of 3 and 10, respectively, in the middle‐ and low‐latitude and auroral regions when meteoric ions are included. The distribution of Pedersen and Hall conductances becomes axisymmetric in the middle‐ and low‐latitude regions. Enhanced axisymmetric ionospheric conductance should impact magnetospheric plasma convection. The contribution of meteoric ions to the ionospheric conductance is expected to be important only on Jupiter in our solar system because of Jupiter's intense magnetic and gravitational fields. Key Points: Meteoric ions dominate the Jovian lower ionosphere due to their long lifetimes Pedersen and Hall conductances are enhanced, and they are independent of local time due to the large concentrations of meteoric ions The contribution of meteoric ions to conductance results from their large densities and altitudinal coincidence with the conductive layer